PENGARUH INSEKTISIDA BOTANI BERBENTUK SERBUK BIJI TERHADAP HAMA KUMBANG Callosobruchus chinensis L. (Coleoptera: Bruchidae) PADA BENIH KACANG HIJAU - Putri Mustika Sari, Sari; Yuswani Pangestiningsih; Syahrial Oemry (Jurnal Agroekoteknologi, 2013)
The effect of botanical insecticides seeds powder againts pest of kumbangCallosobruchus chinensis L. (coleoptera: bruchidae) for the green bean seeds.The objective of this research was to knew the effectiveness of some botanical insecticides onmortality C. chinensis, and green bean seeds weight decrease. The experiment was conductedin the Laboratory Plant Pests, Faculty of Agriculture, University of Sumatra Utara, Medan.Using a completely randomized design (RAL) non factorial with 10 treatments wereF0 (control), F1 (5gr jatropha seeds), F2 (10gr jatropha seeds), F3 (15gr jatropha seeds),F4 (5gr soursop seeds), F5 (10gr soursop seeds), F6 (15gr soursop seeds),F7 (5gr noni seeds), F8 (10gr noni seeds) and F9 (15gr noni seeds) per 500gr of bean greenseeds with three replications. The results showed that 15gr jatropha seeds is the mosteffective in increased mortality imago C. chinensis (93.33%), and green bean seeds weightdecreased as low as (0.37%). The followed by treatments of 15gr soursop seeds, 10grjatropha seeds, 10gr soursop seeds, and 15gr noni seeds, while treatments of5gr jatropha seeds, 5gr soursop seeds, 5gr and 10gr noni seeds less effective.Keywords : Callosobruchus chinensis, botanical insecticides, green bean seeds.